2017
DOI: 10.1002/jmor.20686
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and ecomorphology of emarginate primary feathers

Abstract: Wing tip slots are a distinct morphological trait broadly expressed across the avian clade, but are generally perceived to be unique to soaring raptors. These slots are the result of emarginations on the distal leading and trailing edges of primary feathers, and allow the feathers to behave as individual airfoils. Research suggests these emarginate feathers are an adaptation to increase glide efficiency by mitigating induced drag in a manner similar to aircraft winglets. If so, we might expect birds known for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, it has been shown that the presence of slotted tips in the Jackdaw lead to the formation of multi-cored tip vortices that resulted in a spread of vorticity [23]. Further, it has been hypothesized that slotted feathers in bird wings evolved to reduce the power cost of take-off and landing in terrestrial or coastal/freshwater birds [24]. Despite contradictory findings on the exact role of slotted wing tips, it remains well established that they lend advantages such as lower drag, enhanced lift, postponement of stall and longitudinal stability to bird flight [21,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the presence of slotted tips in the Jackdaw lead to the formation of multi-cored tip vortices that resulted in a spread of vorticity [23]. Further, it has been hypothesized that slotted feathers in bird wings evolved to reduce the power cost of take-off and landing in terrestrial or coastal/freshwater birds [24]. Despite contradictory findings on the exact role of slotted wing tips, it remains well established that they lend advantages such as lower drag, enhanced lift, postponement of stall and longitudinal stability to bird flight [21,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most birds have some degree of slotting at the wing tips that allow feathers to function as individual aerodynamic surfaces [11][12][13][14][15]. In these feathers, asymmetric reductions in the leading and trailing vanes of the feathers provide separation for the feathers to bend, twist, and sweep relatively independently.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we investigated how aerodynamic loading influenced three-dimensional feather deflection, and how that deflection influenced force production for primary feathers from seven raptor species. These species exhibit slotted primary feathers and routinely engage in flap-gliding or soaring flight [12,15]. We also used a rigid Clark-Y airfoil to compare aerodynamics of feather deflection to a similarly sized airfoil that does not deflect.…”
Section: Introductionmentioning
confidence: 99%
“…This specialized form of take flight is facilitated by the shape of the wing tip, specifically the shape and properties of the distal primary feathers (Nudds, Kaiser & Dyke, 2011). The wing surface, shape and a bird's weight set the basic aerodynamic constraints for flight (Henningsson, Hedenström & Bomphrey, 2014), so that the relationships between total wing length, primary feather length and weight define various aspects of flight performance (Muijres et al, 2012;Klaassen van Oorschot, Tang & Tobalske, 2017). Feather structure is also influenced by the flight habit of a species.…”
Section: Introductionmentioning
confidence: 99%
“…We can expect scaled body parameters and balanced aerodynamic performance among agesex classes because successful escape from predators requires equivalent flight capacity in both juveniles and adults of both sexes. Juveniles and females have less mass, while adults and males are larger, requiring the need to compensate for increased weight with greater muscular power and larger wing surfaces to achieve a similar flight speed (Tobalske et al, 2017). We can expect that juveniles and females, being smaller, may be better fliers.…”
Section: Introductionmentioning
confidence: 99%